Persistence of Chlorpyriphos and Deltamethrin Residues in Cabbage - Reddy, C. Narendra; Reddy, D. Jagdishwar (International Journal of Bio-resource and Stress Management, 2011)
The experiment was conducted during kharif -2007 with cabbage variety Varun. Three sprays of chlorpyriphos @ 0.05% and deltamethrin @ 0.01% was sprayed at head formation stage. The dissipation pattern of chlorpyriphos revealed that initial deposit of chlorpyriphos (2.75 mg kg-1) was dissipated below detectable residues at 15 days after third spray. While, in case of deltamethrin, that the initial deposit of cypermethrin (1.21 mg kg-1) was dissipated below detectable level at 7 days after third spray. The maximum residue limit for chlorpyriphos and deltamethrin was found to be 0.5 and 0.2 mg kg-1, respectively. The waiting period for safe harvest of cabbage heads after three sprays of chlorpyriphos (0.05%) and deltamethrin (0.01%) at head formation stage was 6.53 and 1.39 days, respectively. The half life values for chlorpyriphos and deltamethrin was 1.76 and 1.34 days, respectively.